PANDEMICS, TOURISM AND COMMUNITIES: AN ADAPTIVE POLICY FROM A CASE STUDY OF INDONESIA - Vidya Imanuari Pertiwi; Ghulam Maulana Ilman; Revienda Anita Fitrie (Journal of Tourism and Economic, 2021)
This article shed more light on several policies can be adopted by the Indonesian government in terms saving the tourism-communities and tourism itself during Covid-19 pandemic. However, travel restriction policies in various countries also demanded the solidarity of tourists to stay at home, avoiding crowds, and delaying travel plans during the COVID-19 pandemic. It clearly causes the tourism sector to be heavily affected. As a solution , this research used the systematic literature review method to collecting data from 63 article that relevant to this topic. The results of this research classified into three main point that inovation can be raise by re-emphasising alternative forms of tourism through responsible torism and sustainable tourism. Utilization of technology (e-tourism) is a new form of transformation in the tourism sector, it can help tourist screening, case and contact tracing. Therefore, several policy should be created by central to local government that concern about communities sustainability during it’s condition.